Fermentation kinetics and ethanol production from different sweet sorghum varieties - Imam, Tahmina; Capareda, Sergio (International Journal of Agricultural and Biological Engineering, 2011)
Abstract: In recent years bioethanol fuels derived from agricultural biomass resources or waste have been considered the cleanest liquid fuel alternative to fossil fuels. ?Ethanol consumption is expected to reach 11.2 billion gallons by 2012. ?Sweet sorghum, grown in the Southeast and Midwest states in US, contains 14%-20% fermentable sugar and is an ideal feedstock, owing to its ease of fermentation by yeast. ?The objectives of this research were to perform kinetic studies to determine the factors that may affect the rates of sugar consumption and ethanol production during fermentation of two varieties of sweet sorghum juice, Variety 1 (V-1) and Variety 2 (V-2), and to optimize the fermentation efficiency and ethanol production by varying strategies to process the juice before fermentation. ?Kinetic parameters of fermentation provide total sugar consumption rate of 3.4 g/(L